Autoimmune hematological diseases after allogeneic hematopoietic stem cell transplantation in children: an Italian multicenter experience. - Faraci, Maura; Zecca, Marco; Pillon, Marta; Rovelli, Attilio; Menconi, Maria Cristina; Ripaldi, Mimmo; Fagioli, Franca; Rabusin, Marco; Ziino, Ottavio; Lanino, Edoardo; Locatelli, Franco; Daikeler, Thomas; et al. (Biol Blood Marrow Transplant, 2014)
Autoimmune hematological diseases (AHDs) may occur after allogeneic hematopoietic stem cell transplantation (HSCT), but reports on these complications in large cohorts of pediatric patients are lacking. Between 1998 and 2011, 1574 consecutive children underwent allogeneic HSCT in 9 Italian centers. Thirty-three children (2.1%) developed AHDs: 15 autoimmune hemolytic anemia (45%), 10 immune thrombocytopenia (30%), 5 Evans' syndrome (15%), 2 pure red cell aplasia (6%), and 1 immune neutropenia (3%). The 10-year cumulative incidence of AHDs was 2.5% (95% confidence interval, 1.7 to 3.6). In a multivariate analysis, the use of alternative donor and nonmalignant disease was statistically associated with AHDs. Most patients with AHDs (64%) did not respond to steroids. Sustained complete remission was achieved in 87% of cases with the anti-CD20 monoclonal antibody (rituximab). Four patients (9%) (1 autoimmune hemolytic anemia, 1 Evans' syndrome, 2 immune thrombocytopenia) died at a median of 87 days after AHD diagnosis as a direct or indirect consequence of their disorder. Our data suggest that AHDs are a relatively rare complication occurring after HSCT that usually respond to treatment with rituximab.
Keywords: Child; Child, Preschool; Female; Hematologic Diseases; Hematopoietic Stem Cell Transplantation; Humans; Italy; Male; Remission Induction; Risk Factors; Transplantation Conditioning

Allogeneic hematopoietic stem cell transplantation for Philadelphia-positive acute lymphoblastic leukemia in children and adolescents: a retrospective multicenter study of the Italian Association of Pediatric Hematology and Oncology (AIEOP). - Fagioli, Franca; Zecca, Marco; Rognoni, Carla; Lanino, Edoardo; Balduzzi, Adriana; Berger, Massimo; Messina, Chiara; Favre, Claudio; Rabusin, Marco; Lo Nigro, Luca; Masetti, Riccardo; Prete, Arcangelo; et al. (Biol Blood Marrow Transplant, 2012)
Philadelphia-positive acute lymphoblastic leukemia (Ph+ ALL) still represents a major challenge. We report the experience of the Italian Association of Pediatric Hematology and Oncology (AIEOP) with allogeneic hematopoietic stem cell transplantation (HSCT) in children with Ph+ ALL from 1990 to 2008. Sixty-nine patients received HSCT from either a related (37, 54%) or an unrelated (32, 46%) donor. Twenty-five patients (36%) underwent transplantation before 2000 and 44 (64%) after 2000. Twenty-three patients (33%) received Imatinib mesylate treatment before HSCT and seven (10%) after HSCT. After a median follow-up of 56 months, the overall survival (OS) probability was 51% (95% confidence interval [CI], 38-63), the leukemia-free survival (LFS) was 47% (95% CI, 34-59), transplantation-related mortality (TRM) was 17% (95% CI, 10-30), and relapse incidence (RI) was 36% (95% CI, 26-50). Transplantation in first complete remission, female gender, and lower WBC count at diagnosis were associated with a better LFS in both univariate and multivariate analyses. Patients with p210 transcript had a trend for a worse prognosis compared with those who had the p190 transcript. Our series confirms the role of HSCT in the eradication of Ph+ ALL. Early HSCT is recommended once morphologic remission is obtained.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Benzamides; Child; Child, Preschool; Disease-Free Survival; Drug Administration Schedule; Female; Fusion Proteins, bcr-abl; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Humans; Infant; Italy; Male; Philadelphia Chromosome; Piperazines; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Pyrimidines; Remission Induction; Retrospective Studies; Secondary Prevention; Transplantation, Homologous; Young Adult